2008
DOI: 10.1002/ca.20620
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of sinus flow in the confluence of sinuses

Abstract: The confluence of sinuses (CS; torcular herophili) is represented by the junction of the superior sagittal (SSS), straight (SS), occipital (OS), and two transverse sinuses (TS). The objective of this study was to interpret sinus flow around the CS by morphological investigation of the sinuses. This study is based on visual examination of dural venous sinuses in the region of the CS in 31 adult cadavers. In the inflow zone, we examined the direction of SSS and SS flow. In the communication zone, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
0
21
0
5
Order By: Relevance
“…Another anatomic study by Park et al showed right dominance in 35.5% and symmetry in 58.1%. 15 A study based on CT scans by Friedmann et al 7 showed that the right-sided venous dominance was most common (70-80%), and the venous system was larger in men than women. A study based on magnetic resonance venography by Manara et al, 23 showed that the mean caliber of the right TS was significantly greater than the contralateral sinus (6.5 mm +/-1.84 vs. 5.1 mm +/-1.72).…”
Section: Discussionmentioning
confidence: 99%
“…Another anatomic study by Park et al showed right dominance in 35.5% and symmetry in 58.1%. 15 A study based on CT scans by Friedmann et al 7 showed that the right-sided venous dominance was most common (70-80%), and the venous system was larger in men than women. A study based on magnetic resonance venography by Manara et al, 23 showed that the mean caliber of the right TS was significantly greater than the contralateral sinus (6.5 mm +/-1.84 vs. 5.1 mm +/-1.72).…”
Section: Discussionmentioning
confidence: 99%
“…30 The anomalies occurring in the SS might extend to the CS through the septa, which are residues of the dural wall formed in the course of development of the sinuses of the posterior fossa. 28 The presence of such septa might direct the venous flow in various directions toward and away from the CS. 28 The fact that septa were found in three (13.63%) specimens in the present series led us to believe that they extended to the torcula and directed the venous blood flow toward the left TS and right TS rather than directly toward the CS.…”
Section: Discussion Morphological Findingsmentioning
confidence: 99%
“…28 The presence of such septa might direct the venous flow in various directions toward and away from the CS. 28 The fact that septa were found in three (13.63%) specimens in the present series led us to believe that they extended to the torcula and directed the venous blood flow toward the left TS and right TS rather than directly toward the CS. An example of this situation was found in Specimen 1, the posterior portion of which exhibited a septum adhering to the posterior wall of the CS.…”
Section: Discussion Morphological Findingsmentioning
confidence: 99%
“…These investigators determined the direction, communication and type of inflow for the straight sinus at the CS, features which could impact on the feasibility of selective catheterization of the straight sinus from the transverse sinus. They found that, in 58.1%, the direction of straight sinus inflow was toward the center of the CS, in 35.5% it was toward the left transverse sinus, in 3.2% it was toward an occipital sinus and in only 3.2% was it toward the right straight sinus 21. This anatomy suggests that in many cases, particularly from a right transverse sinus approach, a relatively acute reverse turn must be navigated in order to enter the straight sinus.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al 21 evaluated the morphology of the CS in a cadaver study and concluded that the CS should not be regarded simply as the drainage site for the superior sagittal and straight sinus or the origin of the transverse sinuses, but rather as a complex system of anastomosing sinuses 21. These investigators determined the direction, communication and type of inflow for the straight sinus at the CS, features which could impact on the feasibility of selective catheterization of the straight sinus from the transverse sinus.…”
Section: Discussionmentioning
confidence: 99%